Cover Picture: Chemisorption of a Strained but Flexible Molecule: Cyclooctyne on Si(001) (Chem. Eur. J. 23/2017). Issue 23 (1st March 2017) - Pecher, Josua; Schober, Christoph; Tonner, Ralf
Abstract : Chained to the surface of a semiconductor : Computational analysis reveals why cyclooctyne binds so strongly to the Si(001) surface. Ring strain and conformational flexibility are identified as decisive factors that differentiate this system from the adsorption of smaller molecules. Furthermore, the system acts as a prototype for the construction of organic/semiconductor interfaces, which promise to enhance the application range of electronic devices. More information can be found in the Full Paper by R. Tonner, et al. onpage 5459 ff.